Computational dynamic analysis of vibrational conveyers with single-mass;: Crank-and-rod excitersle - Alisverisci, G. Fuesun (AMER INST PHYSICS, 2007)
The conveyers has a trough supported on elastic stands which are rigidly fastened to the trough and a supporting frame. The trough is oscillated by a common crank drive. This vibration cause the load to move forward and upwards. These moving load jumps periodically and move forward by little vibration. Movement is strictly related to vibration parameters. This is applicable in laboratory conditions with a few gram of loads till tons of loading capacity in the industry. In this work the changes of the quantity of motion parameters have been represented by graphics using mathematica software. Obtained results are compared the results in the literature and it is realized the general tendency are approximately same.
Keywords: vibrational (shaking) conveyers; crank-and-rod mechanism; operation mode; Physics